Law and representation in early modern drama - Mukherji, Subha (Cambridge University, 2013)
This examination of the relation between law and drama in Renaissance England establishes the diversity of their dialogue, encompassing critique and complicity, comment and analogy, but argues that the way in which drama addresses legal problems and dilemmas is nevertheless distinctive.